2018
DOI: 10.1212/cpj.0000000000000517
|View full text |Cite
|
Sign up to set email alerts
|

Presentation, etiology, and outcome of brain infections in an Indonesian hospital

Abstract: BackgroundLittle detailed knowledge is available regarding the etiology and outcome of CNS infection, particularly in HIV-infected individuals, in low-resource settings.MethodsFrom January 2015 to April 2016, we prospectively included all adults with suspected CNS infection in a referral hospital in Jakarta, Indonesia. Systematic screening included HIV testing, CSF examination, and neuroimaging.ResultsA total of 274 patients with suspected CNS infection (median age 26 years) presented after a median of 14 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
3
19
2
2
Order By: Relevance
“…4 In Indonesia, TE is still the main CNS disorder in AIDS patients followed after Tuberculous meningitis. 5 A definitive diagnosis of TE can be provided by brain biopsy and finding T. gondii tachyzoites. The examination is an invasive procedure and associated with a significant increase in morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…4 In Indonesia, TE is still the main CNS disorder in AIDS patients followed after Tuberculous meningitis. 5 A definitive diagnosis of TE can be provided by brain biopsy and finding T. gondii tachyzoites. The examination is an invasive procedure and associated with a significant increase in morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Imran et al . reported that tuberculosis, toxoplasmosis, and cryptococcosis are common causes of CNS infections in adult patients in a referral hospital in Jakarta, Indonesia [ 9 ]. Therefore, this study aimed to isolate, identify and determine the serotype of S. pneumoniae strains in cerebrospinal fluid (CSF) from patients clinically diagnosed with CNS infection at a national referral hospital, Jakarta, Indonesia.…”
mentioning
confidence: 99%
“…3 An insidious onset of non-specific prodromal symptoms followed by a slowly progressive meningitis makes diagnosis challenging, with a wide differential especially in HIV co-infection. 4 Delayed diagnosis and treatment lead to poor outcomes. 5 Inflammatory pathways are not completely understood.…”
Section: Panel 1: Pathophysiologymentioning
confidence: 99%